2007
DOI: 10.1177/14759217070060030201
|View full text |Cite
|
Sign up to set email alerts
|

Strain and Temperature Monitoring of Asymmetric Composite Laminate using FBG Hybrid Sensors

Abstract: Fiber Bragg grating (FBG) hybrid sensors and thermocouples measure strain and temperature simultaneously during and after cure of asymmetric cross-ply composite laminates. FBG strain sensor is used to measure strain; FBG temperature sensor and thermocouple are used to measure temperature. The characteristic matrix of the sensor is derived analytically and measurements can be done without sensor calibration experiments. A wavelength-swept fiber laser is used as the light source. Two FBG hybrid sensors and two K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 19 publications
(17 reference statements)
0
14
0
Order By: Relevance
“…However, compensation techniques are required because of the temperature sensitivity of FBGs. Generally, the FBG strain sensor is used together with an FBG temperature sensor …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, compensation techniques are required because of the temperature sensitivity of FBGs. Generally, the FBG strain sensor is used together with an FBG temperature sensor …”
Section: Introductionmentioning
confidence: 99%
“…Generally, the FBG strain sensor is used together with an FBG temperature sensor. 25 Devices that use core diameter mismatch (CDM) such as single-mode-multimode-single-mode (SMS) fibers have been just suggested as fiber sensors in response to their simple manufacturing and inexpensive cost. [26][27][28][29] These SMS sensors are developed by splicing a piece of multimode fiber (MMF) between two single mode fibers (SMFs).…”
Section: Introductionmentioning
confidence: 99%
“…The Fiber Bragg grating (FBG) sensor, due to its high sensitivity, resistance to electromagnetic interference, good durability, low cost, and more importantly capability of real-time monitoring, has become a widely accepted sensing alternative for strain [27][28][29], temperature [29][30][31], and possibly crack measurements [32,33] in civil engineering fields. Studies of using FBG sensors in crack detection on concrete and metallic structures had shown that distinguishable data alter could be observed when cracks initiated.…”
Section: Introductionmentioning
confidence: 99%
“…For optical fiber strain sensors to be accurate and practical, it is necessary to separate the mechanical strain from the thermal effect. Several techniques have been proposed for the mechanical strain and temperature discrimination, such as the reference-grating technique [9], the dual-wavelength technique [10] and the hybrid-grating technique [11]. To separate the mechanical strain from the temperature effect, it is necessary to determine the thermal strain of the optical fiber sensor when the host structure is subjected to a temperature change.…”
Section: Introductionmentioning
confidence: 99%